Efficacy of Rodenticides for Roof Rat and Deer Mouse Control in Orchards - Quinn, Niamh Niamh; Davis, David H.; Engeman, Richard M.; Baldwin, Roger A. (DigitalCommons@University of Nebraska - Lincoln, 2014)
Roof rats and deer mice are occasional pests of orchard crops throughout the world. The application of rodenticides is an effective and practical method for controlling rodent pests and reducing damage. However, a paucity of information exists on the efficacy of rodenticides in orchards for these pest species. To address this gap in knowledge, we first developed an index to measure rodent activity in order to monitor efficacy of rodenticides. We then used this index to test the efficacy of 3 first-generation anticoagulant rodenticide baits to determine their utility for controlling roof rats and deer mice in agricultural orchards. Of the baits tested, the 0.005% diphacinone grain bait was the most effective option for controlling both roof rats and deer mice (average efficacy = 90% and 99%, respectively). The use of elevated bait stations proved effective at providing bait to target species and should substantially limit non-target access to rodenticides.